DUAL BANKING SYSTEM PASKA MERGER DI INDONESIA - Arivatu Ni'mati Rahmatika; Nurvita Putri Romadhani (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2021)
This article explains that (1) The Post-Merger Dual Banking System is banking that has been implemented in Indonesia. Management of assets together with third party funds with large incomes that have been obtained from conventional banks and Islamic banks, third party funds that run accordance with funding and lending. Conventional banks and Islamic banks provide credit financing to MSMEs (Micro, Small and Medium Enterprises) and differentiate in operations between conventional banks and Islamic banks, (2) this study aims to determine the concept of managing and distributing funds in the dual banking system in Indonesia before and after the merger, (3) the method used is a qualitative method in the form of a library (library research), (4) the results of the study that between Islamic and post-merger conventional banks continue to operate credit funds to the public.